The effect of Sn content on mechanical, magnetization and shape memory behavior in NiMnSn alloys - Aydogdu, Y.; Turabi, A. S.; Kok, M.; Aydogdu, A.; Yakinci, Z. D.; Aksan, M. A.; Karaca, H. E. (Elsevier Science Sa, 2016)
The effects of the composition alteration on the magnetization and shape memory behavior of Ni50Mn40-xSn10+x (x = 0, 1, 2, 3) alloys were systematically investigated by thermal, magnetic and mechanical experiments. Phase transformation from ferromagnetic austenite to weakly magnetic martensite was observed during thermal cycling under magnetic field and transformation temperatures were decreased with increasing Sn (or decreasing Mn). Moreover, the saturation magnetization of martensite increased with Sn content. Ni50Mn40Sn10 showed the recoverable strain of 2.1% during thermal cycling under 300 MPa and the reversible superelastic strain of 2% at 190 degrees C. Mechanical experiments exhibited that the largest compressive deformation of about 7% at 650 MPa occurred in Ni50Mn39Sn11 while Ni50Mn40Sn10 had fractured at 4% and 390 MPa at room temperature. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Shape memory; Composition alteration; Superelasticity; Phase transformation; Saturation magnetization